PENAMBAHAN BAKTERI PROBIOTIK (Bacillus sp) ISOLASI DARI GIANT RIVER FRAWN (Macrobrachium rosenbergii, de man) DI FEED BUATAN UNTUK MENINGKATKAN PERTUMBUHAN IKAN BAUNG (Hemibagrus nemurus) - Sainah Sainah; Adelina Adelina; Benny Heltonika (Berkala Perikanan Terubuk, 2016)
The aims of this research was to knows the effect of probiotic bacteria additon which isolated from giant river prawn (Macrobrachium rosenbergii, de man) with different dose in artificial feed on growthand feed efficiency of green catfish (Hemibagrus nemurus). This research used Completely Randomized Design (CRD) with one factor, four treatments and three replications. The treatments were addition of probiotic bacteria in artificial feed with different dose is, P0 (without addition of probiotic), P1 (5 ml/kg of feed), P3 (10 ml/kg of feed) and P3 (15 ml/kg of feed). Probiotic given throught in artificial feed with 35% protein content. The results showed the treatments in P2 (10 ml/kg of feed) were the best treatment with digestibility of feed 51,46%, feed efficiency 29,02%, protein retention 71,57%, specific growth rate 2,18% and survival rate 91,67%.